Investigation of quantum trajectories in photosynthetic light harvesting through a quantum stochastic approach - Teerapat Uthailiang; Ongart Suntijitrungruang; Purin Issarakul; Peera Pongkitiwanichakul; S. Boonchui (Scientific Reports)
Abstract In natural photosynthesis systems, pigment-protein complexes harvest the photon from sunlight with near-unity quantum efficiency. These complexes show incredible properties that cannot be merely extrapolated from knowledge of their composition. Additionally, the environment perturbing the light-harvesting process significantly affects the mechanism of photosynthesis. This research investigates the photosystem II reaction center (PSII RC) from a new perspective which considers the restricted path of the exciton transfer, in the photosynthesis system, as a quantum trajectory picture with the quantum continuous measurement. In this work, the corridor path of exciton transfer dynamics satisfies the equation of motion, as the spin dynamics, which consists of precession, relaxation, and random force rapidly fluctuating spin splitting arising from the bath. Moreover, the width of the corridor is an important factor for restricting path dynamics resulting in the localization and decoherence phenomenon. Our method is to analyze exciton transfer dynamics through paths on the Bloch sphere, in order to investigate the propagating states in accordance with the weight functional which depends on the coupling parameter between the system and environment as the phonon bath. Our results show that the paths outside the width of the corridor have a considerably lower weight functional and decoherence functional than those inside the width. Therefore, the degrees of localization, the weight functional, and the decoherence functional are related. Furthermore, the simulation reveals three characteristics of exciton transfer: gradual transfer, no transfer, and rapid transfer, relying significantly on the coupling between the system and phonons.